Medicinal plants with mosquitoes repellent activity: a systematic review (Research, Society and Development, 2022)
Repellents are important allies in trying to prevent diseases transmitted by mosquito bites. Plants have been a source of various repellents and insecticides because they have a large reservoir of bioactive substances, in addition, their products have already been tested and are gaining space in research as a low-cost and easy-access alternative. A systematic review was carried out in the databases, Science Direct, Scielo, SciFinder, Springer, PubMed / Medline, Scopus and Web of Science, evaluated by three reviewers. Titles, abstracts and articles were analyzed in full in English, Spanish and Portuguese. To identify the articles, the following descriptors from the Medical Subject Headings (MeSH) were used: “insect repellents”, “essential oils”, “plants extract”, “repellent activity”, mosquitoes and plants. The bibliographic search resulted in 2274 records. Of these, 27 abstracts were considered potentially relevant, and at the end of the selection, 17 articles were included in their entirety. It was found that medicinal plants showed repellent activity against various species of mosquitoes, however due to the little standardization of the methodologies used and the products obtained it is necessary to develop standardized methods to guarantee the quality and reproducibility of clinical trials with medicinal plants.